Pengembangan Keterampilan Berkreasi dan Berinovasi dalam Pembelajaran Bahasa di SD melalui Program Inservice Training Berbasis Hasil Penelitian - Kasihani K.E. Suyanto; Bambang Yudi Cahyono; Muhana Gipayana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: This R & D study aims at developing teachers skills to be more creative and innovative during their language classes in primary  schools. The study was conducted to confirm the results of previous studies which indicate that there are still many teacher are not sufficiently qualified as language teachers. To improve the situation some in-service training materials have been developed. They are (1) practical techniques of teaching English for young leaners, (2) telling and reading stories in English, (3) classroom action research and its procedures, (4) writing Indonesian composition, (5) the use of spelling in Indonesian composition.